Proyecto de producción y comercialización de íconos nacionales a base de material reciclado para la ciudad de Guayaquil - Escobar Pazmiño, Navia Paredes (2009)
In the present project it is realised a study of market and financial feasibility for the implementation of a company in Guayaquil city, that produce and commercializes figures done with recycling material, such as metal, plastic, wood, among others, that represents or personifies Ecuador regions. Located in artisan markets, commercial centers and airport basing us on the perceptions, tastes and preferences of the persons, using manpower of local craftsmen who will develop the product with recyclable materials, giving a new introduction for the renewable development of this type of art in which it protects the environment, doing it brings back consciousness in an ecological vision of the world in the citizenship, between diverse measures for the conservation of natural resources of the Earth. The study includes an analysis of financial viability to detail the costs that imply the creation and development of a production and commercialization of this type, the income we anticipated to obtain and from that structure, with financial criteria and based on a market study, the convenience of the project.